Ugaritic: The Ugaritic šumma izbu Text - Pardee, Dennis
ersch. 1987; RS 24.247+; Ugaritica VII 44-60; KTU 1.103 + 1.145. Appendix III (p. 147): The Ugaritic Omen Text Based on Anomalous Human Births, RS 24.302; Ugaritica VII 60-62; KTU 1.140; DO 6633.